BIROKRASI PEMERINTAH DAERAH JAKARTA MENDORONG INKLUSIVITAS HAK KERJA BAGI PENYANDANG DISABILITAS DALAM SEKTOR FORMAL - Watanata, Ghaniya Raisa; Tan, Josephine Milhan; Nugraha, Dwi Putra (MAKSIGAMA, 2025)
The absorption of persons with disabilities into the workforce in Indonesia remains low. As the capital city, Jakarta plays a strategic role in promoting work inclusivity for persons with disabilities and setting an example for other regions. According to the Jakarta Social Service Agency, in 2019, there were 14,471 registered persons with disabilities in the region. To enhance employment accessibility, the Jakarta Provincial Government has taken progressive measures, including the establishment of the Disability Service Unit (Unit Layanan Disabilitas or ULD) in the employment sector and coordination with various related institutions. Another initiative is the Inclusive Job Center (IJC), which aims to connect persons with disabilities with companies willing to employ them, fostering an Inclusive Labour Market (ILM). This study employs a normative legal research method with a statute approach. The data used is secondary data obtained through a literature study, encompassing primary, secondary, and tertiary legal sources. The findings indicate that while various policies have been developed to enhance workforce inclusivity for persons with disabilities, implementation challenges remain, particularly in employer awareness and workplace accessibility. Therefore, strengthening policies and enhancing oversight are necessary to ensure the effectiveness of regulations in creating an inclusive labor market. Keywords: Local Government Bureaucracy, Persons with Disabilities, Work Inclusion, Disability Service Unit, Inclusive Job Center